KARIES GIGI ANAK AKIBAT IBU HAMIL KURANG GIZI - Ni Made Sirat (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2017)
Tooth function is helping the function of spech, face shape, and tools of mastication. Early tooth development occurs during a six-week-old fetus. Diet in pregnant women can affect fetal growth and development of teeth. Prevention of tooth decay in baby begins before birth and continues after birth. Caries and periodontal disease is dental and oral diseases are most commonly suffered. This literature study aims to determine the nutrition of pregnant women as a cause of dental caries. Malnutrition during pregnancy can cause serious problems, including email hypoplasia. Enamel hypoplasia is an incomplete form from enamel. Enamel hypoplasia is clinically meaningful cause tooth decay and caries affecting vulnerability. Dental caries affects on weight loss, growth, and quality of life in children - preschoolers. Prevention of dental caries can done pre-eruption and post-eruption of the teeth. Conclusion: malnutrition during pregnancy can cause enamel hypoplasia. Enamel hypoplasia susceptible to caries. Dental caries affects on weight loss, growth, and quality of life in children - preschoolers, which in turn lowers the quality of human resources